2001
DOI: 10.1017/s1049023x00043417
|View full text |Cite
|
Sign up to set email alerts
|

Post-War Kosovo: Part 2. Assessment of Emergency Medicine Leadership Development Strategy

Abstract: Since the return of the refugee population to Kosovo, attempts at development of an emergency medical system in Kosovo have met with varied success, and have been hampered by unforeseen barriers. These barriers have been exacerbated by the lack of detailed health system assessments. A multimodal approach of data collection and analysis was used to identify potential barriers, and determine the appropriate level of intervention for emergency medicine (EM) development in Kosovo. The four step, multi-modal, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…As a result of studies on emergency services in Kosovo, developmental programs similar to those suggested here have been successfully implemented to improve the training in and provision of Kosovo's emergency medical services [13]. Visiting experts currently travel to the province to provide didactic and bed-side training to physicians and other health care providers on the latest advances in emergency medicine, internal medicine, pediatrics, and several other fields of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of studies on emergency services in Kosovo, developmental programs similar to those suggested here have been successfully implemented to improve the training in and provision of Kosovo's emergency medical services [13]. Visiting experts currently travel to the province to provide didactic and bed-side training to physicians and other health care providers on the latest advances in emergency medicine, internal medicine, pediatrics, and several other fields of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…7 The EM system in Kosovo, Federal Republic of Yugoslavia, after a civil war was found to be underdeveloped. 8 Little formal training, lack of organization, equipment, and a reliable communication system and lack of centralized emergency centers were identified early on as barriers to ideal health care. 9 A group from the United States suggested that limited specialized training, lack of coordination between departments, and failure to establish a medical records system were some of the barriers to provision of care in the highvolume and high-acuity PEM system in Kosovo.…”
Section: Other Developing Pem Settingsmentioning
confidence: 99%
“…2 The application of assessment methods complementing humanitarian assistance in Kosovo have been explored previously in emergency medicine and public health efforts by Johns Hopkins and the International Rescue Committee. [3][4][5][6] From a broader perspective, in an era of increasing humanitarian and post-crisis intervention throughout the world, assessments before intervention and evaluations post intervention become increasingly important to donors, academicians, politicians and administrators.…”
Section: Importancementioning
confidence: 99%